Hospital mergers with regulated prices - Brekke, Kurt R. (2014)
We study the effects of a hospital merger using a spatial competition framework with semialtruistic hospitals that invest in quality and expend cost-containment effort facing regulated prices. We find that the merging hospitals always reduce quality, whereas non-merging hospitals respond by increasing (reducing) quality if qualities are strategic substitutes (complements). A merger leads to higher average treatment cost efficiency and, if qualities are strategic substitutes, might also increase average quality in the market. If a merger leads to hospital closure, the resulting effect on quality is positive (negative) for all hospitals in the market if qualities are strategic substitutes (complements). Whether qualities are strategic substitutes or complements depends on the degree of altruism, the effectiveness of cost-containment effort, and the degree of cost substitutability between quality and treatment volume.